Effects of Cathepsin S Inhibition in the Age-Related Dry Eye Phenotype (2023)
ABSTRACT: Purpose: Aged C57BL/6J (B6) mice have increased levels of cathepsin S, and aged cathepsin S (Ctss-/-) knockout mice are resistant to age-related dry eye. This study investigated the effects of cathepsin S inhibition on age-related dry eye disease. Methods: Female B6 mice aged 15.5 to 17 months were randomized to receive a medicated diet formulated by mixing the RO5461111 cathepsin S inhibitor or a standard diet for at least 12 weeks. Cornea mechanosensitivity was measured with a Cochet-Bonnet esthesiometer. Ocular draining lymph nodes and lacrimal glands (LGs) were excised and prepared for histology or assayed by flow cytometry to quantify infiltrating immune cells. The inflammatory foci (>50 cells) were counted under a 10× microscope lens and quantified using the focus score. Goblet cell density was investigated in periodic acid-Schiff stained sections. Ctss-/- mice were compared to age-matched wild-type mice. Results: Aged mice subjected to cathepsin S inhibition or Ctss-/- mice showed improved conjunctival goblet cell density and cornea mechanosensitivity. There was no change in total LG focus score in the diet or Ctss-/- mice, but there was a lower frequency of CD4+IFN-γ+ cell infiltration in the LGs. Furthermore, aged Ctss-/- LGs had an increase in T central memory, higher numbers of CD19+B220-, and fewer CD19+B220+ cells than wild-type LGs. Conclusions: Our results indicate that therapies aimed at decreasing cathepsin S can ameliorate age-related dry eye disease with a highly beneficial impact on the ocular surface. Further studies are needed to investigate the role of cathepsin S during aging.